Chimeric vaccine design against the conserved TonB-dependent receptor-like β-barrel domain from the outer membrane tbpA and hpuB proteins of Kingella kingae ATCC 23330 - Mashraqi, Mutaib M.; Alzamami, Ahmad; Alturki, Norah A.; Almasaudi, Hassan H.; Ahmed, Ibrar; Alshamrani, Saleh; Basharat, Zarrin (Frontiers in Molecular Biosciences, 2023)
Kingella kingae is a gram-negative bacterium that primarily causes pediatric infections such as septicemia, endocarditis, and osteoarticular infections. Its virulence is attributed to the outer membrane proteins having implication in bacterial adhesion, invasion, nutrition and host tissue damage. TonB dependent receptors (TBDRs) have an important role in nutrition and previously implicated as vaccine targets in other bacteria. Therefore, we targeted the conserved β-barrel TBDR domain of these proteins for designing a vaccine construct that could elicit humoral and cellular immune response. We used bioinformatic tools to mine TDR containing proteins from K. kingae ATCC 23330 and then predict B and T-cell epitopes from their conserved β-barrel TDR domain. A chimeric vaccine construct was designed using three antigenic epitopes, covering >98% of world population and capable of inciting humoral and adaptive immune response. The final construct elicited a robust immune response. Docking and dynamics simulation showed good binding affinity of vaccine construct to various receptors of the immune system. Additionally, the vaccine was predicted to be safe and non-allergenic, making it a promising candidate for further development. In conclusion, our study demonstrates the potential of immunoinformatics approaches in designing chimeric vaccines against K. kingae infections. The chimeric vaccine we designed can serve as a blueprint for future experimental studies to develop an effective vaccine against this pathogen, that can serve as a potential strategy to prevent K. kingae infections.